Solution training - "Baugh, James R." (Gretna, 1980)
Solution Training offers tangible proof that finding workable solutions to problems is a skill that can be developed by the individual or within a business organization. Here is a structured approach that teaches the individual how to identify and define problems, evaluate alternative courses of action, then move toward a solution.
Keywords: Psychology